Theoretical study of the paracetamol adsorption over a graphene oxide sheet - López-Jesús, Beatriz Paulina; Pacheco-Ortin, Sandy María; Agacino-Valdés, Esther (European Journal of Chemistry, 2025)
In recent decades, the detection of non-steroidal anti-inflammatory drugs (NSAIDs) in various water bodies has raised concerns for their environmental impact, since conventional wastewater treatment plants are inefficient for removing these pharmaceutical contaminants. In this way, many researchers have proposed various techniques, including the use of adsorbent materials. In this work, we conducted a theoretical study of the adsorption of the paracetamol (PCT) molecule on a large cluster (C80H26O24) of graphene oxide (GO) that simulates a sheet. The calculations were based on the DFT formalism using the combination M06-2X/6-31G**. The GO sheet used, with a C/O ratio of 3.5 and an oxygen content of 17%, exhibited a high adsorption capacity and stability. The adsorption energies for the most preferred complexes were 22 kcal/mol with adsorption distances between 1.84 and 2.60 Å, which allowed us to conclude that this is a very favored chemisorption process. The interaction distances and adsorption energies obtained were compared with those from other studies, confirming that the DFT approach used in this work, as well as the GO sheet modeled, were suitable. The percentages of elongation of the bonds in the PCT molecule, calculated from the bond distances before and after the adsorption process, evidenced a weakening of certain bonds in the molecule related to its most likely fragmentations. Therefore, it is concluded that these adsorption processes mediated by GO sheets can help, together with other methods, with PCT degradation.